The kinematic potential of music and the perception of musical motion - Voskoboinikova, Yuliia; Konovalova, Iryna; Ginak, Nataliia; Xiaolin, Lu; Chen, Jiang (Edelweiss Applied Science and Technology, 2025)
The article aims to explore the mechanisms by which perceived kinematic properties of music are transformed into specific motor representations. The objectives of this study involve identifying the causes behind the emergence of motor representations that arise during the perception of music. This enables an examination of the physiological, psychological, and pedagogical prerequisites for the formation of motor representations during music performance or listening. Existing research was examined through analytical methods, including contextual, structural, and comparative analysis. The study is based on the method of bibliometric analysis as a general scientific method and the method of interpretology. A comprehensive approach to the problem was employed, incorporating an analysis of interdisciplinary studies. A systems approach was also utilized to establish connections and functions among various types of perception of music’s kinematic potential. Musicological methodology was applied in the study of specific means of musical expression and their influence on the perception of motion. The kinematic potential of music stems from the way the human brain absorbs auditory stimuli. The current integrative approach to performing emphasizes natural sound-movement links, demonstrating them both during practice and on stage. The novelty of this study lies in its departure from the associative paradigm in the perception of musical motion and its emphasis on psychophysiological regularities of kinematic experiences that occur during music performance and listening.